Effects of Winter Cover Crop Mixture and Termination on the Performance and Physiology of cv. Barbera (Vitis vinifera L.) Grapevines - F. Pelusi; M. Gatti; L. Cunial; F. Del Zozzo; S. Santelli; S. Poni (Australian Journal of Grape and Wine Research)
The adoption of winter cover crops (CCs), to be terminated in spring, is gaining popularity in temperate climate viticulture. We evaluated the effects of two novel termination practices—interrow rolling (R) and subrow mulching (SRM)—on vine performance and physiology of Barbera grapevines over 3 years, comparing them to a standard termination practice (green manuring, GM) and a control (C) consisting of alternated tilled and vegetated interrows. For each termination type, we used a cereal-based (Humusfert, H) and a more balanced (Stratus, S) seed cocktail. Data collection included CC biomass, seasonal soil and leaf water potential, leaf assimilation (A) and stomatal conductance (gs) rates, vine vigor, yield, and grape composition at harvest. R caused a 31% reduction in pruning weight compared to C. Soil water potential at 30-cm depth, as well as leaf A and gs, was more limited than in the other treatments and, in S-R, ripening was delayed. R performances might suffer from increased surface evaporation and reduced precipitation effectiveness due to the thick mulch layer. Both SRM treatments ensured a thick mulch layer (over 1 kg of desiccated grass/m2), which effectively controlled weeds when placed under the row. SRM did not impact vine vigor and yield; however, using the S mix slightly delayed final ripening. The presence of a thick, dead mulch layer under the row improved soil water potential (ΨSOIL) at 30- and 60-cm depths compared to all remaining treatments that shared a mowed under-the-trellis strip. Seasonal dynamics of absolute ΨSOIL show that when ΨSOIL in the C plot fell below −0.2 MPa, ΨSOIL was significantly higher (less negative) in H-SRM than in S-SRM. This was also associated with average reductions of 31.3% and 37.1% in A and gs rates in S-SRM compared to H-SRM, respectively. The higher fresh biomass yielded by the more balanced mix (S) may relate to increased soil water depletion, especially during the pre-termination phase. Both C and GM treatments showed similar vine performance; however, C was significantly limited in leaf gas exchange compared to others. C does not benefit from any mulching effect, and a competitive native grass cover persists every second interrow during the dry and harsh summer season.